A Case Report of Esophageal Cancer using the Latissimus Dorsi Muscle Flap with Subcutaneous Fat Tissue for the Repair of the Left Main Bronchial Defect - Kato, Takeshi; Yamamoto, Hitoshi; Endo, Wakio; Kimura, Yutaka; Kikkawa, Nobuteru; Urano, Naomi; Kurokawa, Eiji; Tanigawa, Takahiko; Hayashi, Taro; Goto, Masashi (The Japanese Journal of Gastroenterological Surgery, 2002)
An 81-year-old man was diagnosed with an esophageal cancer in the middle thoracic esophagus. A CT scan and a bronchofiberscopic examination suggested that the cancer might not have invaded the left main bronchus. Following a right lateral thoracotomy without cutting the right latissimus dorsi muscle, a radical esophagectomy was performed, and the membranous wall of the left main bronchus was partially resected because the tumor could not be isolated from the membranous wall. A latissimus dorsi muscle flap with the subcutaneous fat tissue on the distal part was created, and the bronchial defect was covered by the inner side of the muscle flap. No air leakage was noted during positive pressure ventilation or coughing, and the postoperative course was uneventful. We conclude that coverage of the latissimus dorsi muscle flap with subcutaneous fat tissue is a useful technique that can be used to prevent postoperative complications in patients requiring a combined resection of the membranous wall for the treatment of esophageal cancer.